Thrombin’s Esterase Activity in the Presence of Anticoagulant and Other Salts - Roberts, Phyllis S.; Burkat, Rosalind K.; Braxton, W. E (Thrombosis and Haemostasis, 1969)
The rates of hydrolysis of TAME by bovine thrombin were studied in the presence and absence of various salts at 37° in 0.25 M Tris . HCl buffer, pH 8.1, with the following results :1. The rates were inhibited to the same extent in the presence of 0.1 M sodium chloride, citrate, oxalate and sulfate and they averaged 49% of rates in the absence of added salts (controls). In contrast to this, rates in the presence of 0.1 M of the corresponding potassium salts averaged 91 % of the controls.2. 0.01 and 0.1 M LiCl, KC1, NH4C1 or CaCl2 inhibited the rates 5 and 17% respectively but the same concentrations of NaCl inhibited them 14 and 49% respectively. The inhibition by 0.1 M NaCl was not prevented or reversed by the presence of the same concentrations of any of these chlorides, except to a small extent by KCl.3. As the concentration of KC1 or NaCl was increased, the rates fell to minimum values and then increased linearly. The minimum rates occurred in the presence of from 0.15 to 0.4 M salts, and with KC1 they were 85% but with NaCl they were 52% of the controls. With 2.5 M KC1 the rates were 141 % but with 2.5 M NaCl they were 68% of the controls.4. Protamine sulfate (2 or 3 mg/ml) had no significant effects on the reaction when tested at either pH 7.4 or 8.1 (Tris buffers). Inhibition was found only when NaCl was present, whether or not protamine sulfate was also present.Since potassium citrate, oxalate, sulfate and chloride as well as lithium, ammonium and calcium chlorides inhibited the rates only slightly and all to about the same degree, it was concluded that the inhibition was probably due to non-specific ionic strength effects and not to inhibition by any of the anions or cations tested. On the other hand, the inhibitions found in the presence of the sodium salts were concluded to be due only partly to a non-specific ionic strength effect, but primarily to a specific inhibitory effect of Na+.